2021
DOI: 10.1515/hf-2021-0107
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of radial variations in wood properties and comparison of juvenile and mature wood of four common conifers in Mongolia

Abstract: Pinus sylvestris L., Pinus sibirica Du Tour, Picea obovata Ledeb., and Larix sibirica Ledeb. are important forest tree species in Mongolia. The radial variations of wood anatomical characteristics, physical and mechanical properties were evaluated by linear or nonlinear mixed-effects models for effective wood utilization of those of conifers. Many of these wood properties either increased or decreased from the pith to the bark and then became nearly constant based on the selected models. The properties of matu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…As a result, the mean values of annual ring width, basic density, MOE, MOR, and compressive strength were 1.8 mm, 0.40 g/cm 3 , 5.35 GPa, 65.1 MPa, and 28.4 MPa, respectively (Table 4). Except for MOE, these estimated values were similar to those previously obtained in juvenile wood harvested from trees naturally grown in Mongolia (Sarkhad et al 2022). Thus, we conclude that wood obtained from plantation-grown P. sylvestris is not always of lower quality compared to wood from natural forests in Mongolia.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…As a result, the mean values of annual ring width, basic density, MOE, MOR, and compressive strength were 1.8 mm, 0.40 g/cm 3 , 5.35 GPa, 65.1 MPa, and 28.4 MPa, respectively (Table 4). Except for MOE, these estimated values were similar to those previously obtained in juvenile wood harvested from trees naturally grown in Mongolia (Sarkhad et al 2022). Thus, we conclude that wood obtained from plantation-grown P. sylvestris is not always of lower quality compared to wood from natural forests in Mongolia.…”
Section: Resultssupporting
confidence: 87%
“…sic density, 9.41 GPa (96 tonf/cm 2 ) for MOE, 81.7 MPa (833 kgf/cm 2 ) for MOR, and 42.7 MPa (435 kgf/cm 2 ) for compressive strength, respectively. Sarkhad et al (2022) also reported that the basic density, MOE, MOR, and compressive strength of juvenile wood (wood up to about 20 th annual ring from pith) in P. sylvestris trees grown in a natural forest in Mongolia were 0.37 g/cm 3 , 7.64 GPa, 69.4 MPa, and 30.5 MPa, respectively. To compare with previous data, mean values up to the 20 th annual ring from the pith were estimated using obtained fixed-effect models for radial variations (Table 4).…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations